(untitled) (Journal of the College of Education for Women, 2021)
The study aims to examine the problem of forced displacement and its social and economic problems in light of the Syrian crisis. Such an aim helps to know the difficulties and challenges facing the children of displaced families in learning, and the reasons for their lack of enrolment. It also clarifies whether there are significant statistical differences at among the attitudes of the children of the displaced families towards education regarding the following variables: (the work of the head of the family, the economic level of the family, and the work of the children). The study has adopted the descriptive-analytical approach; a questionnaire was adopted as a tool to collect information. The study was applied to a sample of displaced families in Jaramana City in the governorate of Damascus countryside. The sample consisted of sixty items that represent 40% of the displaced families. Results have shown that the largest percentage of the social and economic problems that the displaced families suffer from is due to the high rents of houses and apartments, and to the high prices and the inability to purchase the basic needs. There are statistically significant differences between the attitudes of the children of the displaced families towards education due to the variable of work of the head of the family, and to the variable of the economic level. For the family, the study has recommended, in light of its findings, several recommendations, including: Enacting temporary laws for the displaced families that include: educating their children, giving priority to employing the members of these families, providing them with houses, and granting them easy and interest-free loans that enable them to buy a house or repair their homes when they return to their liberated from terror areas.